Virtual screening and identification of potent phytoconstituents from Acorus calamus L. as inhibitors of Monkeypox virus infection - Shivani Lakhani; Janki V. Rojmala; Nisarginee M. Chotai; Bhargav N. Waghela; Parth Thakor (Journal of Genetic Engineering and Biotechnology)
Background: The threat posed by the Monkeypox (Mpox) disease has re-emerged globally while the world strives to recover from the Corona Virus Disease −19 (COVID-19) pandemic. The World Health Organization has declared Mpox a global health emergency. Monkeypox virus (MPXV), the causative agent of Mpox disease, is a zoonotic, large, enveloped, double-stranded deoxyribonucleic acid (DNA) virus that belongs to the Orthopoxviridae genus. The Food and Drug Administration (FDA), USA has approved repurposed antiviral agents Cidofovir and Tecovirimat as the primary treatment options for Mpox, however, they project systemic toxicity and have underwhelming clinical data. A  plethora of medicinal plant compounds including flavonoids, phenolics, terpenoids, and alkaloids have a wide range of biological activities such as antimicrobial, antioxidant, antiulcer, antineoplastic, anti-inflammatory, and immuno-stimulating potentials. Since many of them are being studied in modern research to discover an active drug candidate, we turned to medicinal plants to explore potent antiviral compounds. Methods: In the present study, we aimed to screen phytoconstituents of Acorus calamus L. (AC) against four essential virulence enabling proteins D8L, A48R, D13L, and A42R of MPXV by in silico approach. Further, we have elucidated pharmaceutical-relevant parameters of hit compounds through their absorption, distribution, metabolism, excretion, and toxicity (ADMET) properties as well as drug-likeness parameters. Results: Our results revealed that AC phytoconstituents such as β-Sitosterol against A42R and D8L, Lucenin-2 against D13L and Zingiberene against A48R showed the strongest binding affinities, respectively. Moreover, Galangin could prominently interact with all four proteins with lower binding energy and higher affinity. All top phytoconstituents obeyed Lipinski’s RO5 and drug-likeness properties. Conclusions: The phytoconstituents of AC can act as potent inhibitors of essential virulence enabling proteins of MPXV. Thus, we recommend further experimental investigations to validate the promising results of the present in silico study.